Mitigasi Bencana Gempa Bumi dengan Metode Learning by Doing Di SMA Negeri 3 Wajo Di Kabupaten Wajo - Habo Abbas, Hasriwiani; Nurbaeti, Nurbaeti; Asrina, Andi (Window of Health : Jurnal Kesehatan, 2022)
Earthguaakes Mitigation by Learning by Doing Method in Senior High School Wajo 3 in Wajo Regency Earthquakes are vibrations of the earth's crust that give vibrations ranging from subtle to shaking. The occurrence of an earthquake is related to the release of tension in the earth's crust which causes elastic waves that propagate across the layers of the earth. The aim of the study was to increase students' knowledge, attitudes and actions towards earthquakes through the learning by doing method of SMA 3 Wajo Kab. Wajo. The research method is a quasi-experimental research. In this study, the experimental group received education through video and simulation media directly and the control group did not receive education. Sampling was done by proportional stratified random sampling but previously calculated the number of samples using the Lemenshow formula, obtained 158 students. The results of this study were pre and post tests, knowledge showed an increase of 41%, attitudes increased by 13%, and actions increased by 25%. The results of this study conclude that the knowledge, attitudes and actions of students have increased this is because the method used is the learning by doing method, namely after being given training, students immediately demonstrate by doing a simulation which in school there really was an earthquake, and here the researcher see his attitude and actions are still not optimal. Therefore, it is recommended that disaster learning be included in the education curriculum where Indonesia is very prone to natural disasters..